Analysis of Soybean’s Marketing Power to Support the Enhancement of Production in Central Java - Oelviani, Renie; Jatuningtyas, Ratih Kurnia (Journal of Economic Education, 2018)
Soybean is one of the strategic commodities in Indonesia. Various internal and external constraints are found in Indonesia’s soybean production. This study aims to analyze the marketing power for supporting the enhancement of soybean production in Central Java. The location selection was done purposively in Grobogan and Wonogiri Districts which are soybean centers in Central Java. The study was conducted in 2014 through a focus group discussion (FGD) approach involving 17 key persons. The data obtained were analyzed using SWOT analysis. The result of SWOT analysis shows that soybean strength priorities in marketing to support the enhancement of soybean production in Central Java are (1) developing seed center to manage the availability of soybean needs in Central Java, including to develop and improve the quantity and quality of soybean produced by the farmers. , (2) soybeans price change based on its quality attributes (3) restriction for importing soybeans to stimulate local soybean cultivation; (4) requiring local soybean promotion agencies to explore potentials and educate the industry and community about local soybeans, (5) group learning and development for the farmer to obtain the best soybean prices, (6) soybean purchasing program at the local government production center for the local soybean processing industry.